Analysis of drug treatment methods for Alzheimer’s disease - Liu, Ruihan (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Alzheimer’s disease (AD) has attracted attention from scientists since every year thousands of patients are suffering from this. AD, as the primary cause of dementia, holds 60%–80% of all cases and is associated with deficient cholinergic neurotransmission. The path of discovering methods to tackle it is still a long way to go, because there is not such a method to completely heal this disease and as for drugs therapy. There are some drugs including tacrine, donepezil, galantamine and rivastigmine, which are officially being used and are proved to be slightly effective. This research will discuss the etiology of AD, the development of AD related drugs, the functions and dosages of drugs, as well as their advantages and disadvantages. It can be avoided in the early stages, by gaining a better understanding of the current different drug treatment methods and the changes made in the process, in order to improve the efficiency and prediction after fixation, and thus provide direction for the future development of AD drugs.